National Cancer Control Programmes - Planning, Implementation, Monitoring and Evaluation - Parkin, Maxwell (Indonesian Journal of Cancer, 2008)
National Cancer Control Programmes - Planning, Implementation, Monitoring and EvaluationÂ full text: http://www.scribd.com/doc/45152084/National-Cancer-Control-Programmes-Planning-Implementation-Monitoring-and-Evaluation